Isometric quadriceps strength determines sailing performance and neuromuscular fatigue during an upwind sailing emulation - Bourgois, J. G.; Callewaert, M.; Celie, B.; De Clercq, D.; Boone, J. (Journal of Sports Sciences, 2016)
This study investigates the physiological responses to upwind sailing on a laser emulation ergometer and analyses the components of the physical profile that determine the physiological responses related to sailing level. Ten male high-level laser sailors performed an upwind sailing test, incremental cycling test and quadriceps strength test. During the upwind sailing test, heart rate (HR), oxygen uptake, ventilation, respiratory exchange ratio, rating of perceived exertion (RPE) and lactate concentration were measured, combined with near-infrared spectroscopy (NIRS) and electromyography (EMG) registration of the M. Vastus lateralis. Repeated measures ANOVA showed for the cardio-respiratory, metabolic and muscles responses (mean power frequency [MPF], root mean square [RMS], deoxy[Hb+Mb]) during the upwind sailing test an initial significant increase followed by a stabilisation, despite a constant increase in RPE. Stepwise regression analysis showed that better sailing level was for 46.5% predicted by lower MPF decrease. Lower MPF decrease was for 57.8% predicted by a higher maximal isometric quadriceps strength. In conclusion, this study indicates that higher sailing level was mainly determined by a lower rate of neuromuscular fatigue during the upwind sailing test (as indicated by MPF decrease). Additionally, the level of neuromuscular fatigue was mainly determined by higher maximal isometric quadriceps strength stressing the importance of resistance training in the planning of training.